Job crafting and motivation to continue working beyond retirement age. Issue 5 (12th September 2016) - Lichtenthaler, Philipp Wolfgang; Fischbach, Andrea
Abstract : Purpose: The purpose of this paper is to examine how promotion- and prevention-focussed job crafting impacts the motivation of older employees to continue working beyond retirement age. The authors hypothesized that promotion-focussed job crafting (i.e. increasing social and structural job resources, and challenging job demands) relates positively and prevention-focussed job crafting (i.e. decreasing hindering job demands) relates negatively with motivation to continue working after reaching the official retirement age, and that these relationships are sequential mediated by work sense of coherence and burnout. Design/methodology/approach: Data from 229 older employees (mean age=55.77) were analyzed using structural equation modeling. Findings: Promotion-focussed job crafting was positively and prevention-focussed job crafting was negatively related with employees' work sense of coherence, which was predictive of employees' burnout, which in turn was predictive of motivation to continue working beyond retirement age. Research limitations/implications: Despite the cross-sectional study design, the results unfold how promotion- and prevention-focussed job crafting are related with motivation to continue working beyond retirement age through work sense of coherence and burnout. Practical implications: Given today's aging and shrinking workforce, older employees working beyond their official retirement age are a necessity for organizations' functional capability. The results suggest that organizations should encourage employees' promotion-focussed job crafting and limit prevention-focussed job crafting. Promotion-focussed job crafting facilitates employees' work sense of coherence, which keeps them healthy and motivates older employees to continue working beyond retirement age. Originality/value: This study adds to the literatures on job crafting and motivation to continue working beyond retirement age and explicates intervening processes in this relationship.